In Vitro Drug Release Evaluations of Piroxicam Self-Nanoemulsifying Drug Delivery System (SNEDDS) - Nugroho, Septiawan Adi; Alrayan , Reza; Prasongko, Erfan Tri; Hutami, Shabrina Nindya (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2024)
Introdiction: Piroxicam is Non-Steroidal Anti-Inflammatory Drug that belongs to the BCS Class 2, characterized by low solubility. The SNEDDS (Self-Nanoemulsifying Drug Delivery System) approach for piroxicam is believed to enhance its solubility and accelerate drug release. Aims: This study aims to demonstrate that SNEDDS piroxicam has a faster drug release rate compared to piroxicam powder and commercially available piroxicam capsules. Methods: SNEDDS formulation equivalent to 20 mg of piroxicam, containing a combination of oleic acid, Kolliphor EL, and Transcutol in a ratio of 2:7:4, was tested for drug release using a dissolution method in simulated gastric fluid without enzymes at pH 1.2. The concentration of dissolved drug was measured using a validated spectrophotometric method. Result: At the 45th minute, the dissolution rate of piroxicam SNEDDS reached 101.525%, significantly higher than 47.550% achieved by piroxicam powder and 87,081 % commercially piroxicam capsules at the same time. Additionally, the dissolution efficiency of piroxicam SNEDDS is superior, with a rate of 85.539%, compared to 34.510% for piroxicam powder and 66.17% for commercially available piroxicam capsules. Conclusion: The development of a Self-Nanoemulsifying Drug Delivery System (SNEDDS) for piroxicam has shown promising potential to improve solubility and drug release, as demonstrated by superior in-vitro release rates compared to piroxicam powder and commercial piroxicam capsules